Effect of mRNA formulated with lipid nanoparticles on the transcriptomic and epigenetic profiles of F4/80+ liver-associated macrophages - Chitsuda Pongma; Pornlapat Keawvilai; Atsadang Boonmee; Benjawan Wongprom; Thitiporn Pattarakankul; Chutamath Sittplangkoon; Mohamad-Gabriel Alameh; Patipark Kueanjinda; James Heyes; Kieu Lam; Benjawan Saechue; Kiat Ruxrungtham; et al. (Scientific Reports)
Abstract Delivery of an mRNA formulated with lipid nanoparticles (LNPs) induces robust humoral and cell-mediated branches of the immune response. Depending on the LNP formula, mRNA encoding proteins can be detected in the liver upon intramuscular administration of mRNA/LNP in mice. This study investigated the impact of mRNA/LNP administration on liver-associated macrophages at the transcriptomic and epigenetic levels in a mouse model. An mRNA encoding ovalbumin (OVA) formulated with LNPs, was administered intramuscularly, and a robust OVA-specific antibody was detected in the serum on Day 7. F4/80+ liver-associated macrophages were isolated and subjected to RNA sequencing, which identified 554 genes whose expression levels were altered compared with those in the PBS control group. The expression of genes involved in macrophage inflammatory functions, such as Tnf, Il6 and Marco, were upregulated. Gene ontology enrichment analysis revealed that IL-6/JAK/STAT3 and TNFα/NF-κB hallmarks were significantly enriched, and mRNA/LNP-exposed liver-associated macrophages were characterized as M1-like cells based on the macrophage transcriptomic profiles. Enrichment of the active histone mark H3K4me3 showed that clusters of loci were highly increased in the mRNA/LNP group, indicating an impact of mRNA/LNPs on macrophage epigenetic profiles. The cis-regulatory regions of Tnf, Il6 and Marco showed enrichment of H3K4me3 marks, which correlated well with their increased transcription. Taken together, our data indicated that mRNA/LNP administration via the intramuscular route influences the gene expression and epigenetic profiles of liver-associated macrophages, reflecting its robust ability to induce an immune response.